LEARNING PRESENT FORMS AS RESPONSE TO COVID-19 FOR STUDENTS IN DAARUL MUTI’AH, KAMPUNG CIPUTAT, CILEDUG - Woro Endah Sitoresmi; Velma Alicia (ASOSIASI IDEBAHASA KEPRI, 2022)
This program is designed for the students who study in Islamic Boarding School Daarul Muti’ah, Kampung Ciputat, Tajur, Ciledug in understanding the grammar materials; present forms (present tense, present continuous, present perfect) as a response to learning process during the pandemic COVID-19 because English is one of subjects in the school which needs extra understanding particularly grammar. This program is conducted approximately 1.5 month which started in the beginning of June 2021 until mid of July 2021. The program tries to reveal; 1) the process of learning present forms which is conducted as the response to pandemic COVID-19 for the students who study in Daarul Muti’ah Kampung Ciputat, Tajur, Ciledug and 2) the process of learning present forms can help the students who study in Daarul Muti’ah Kampung Ciputat, Tajur, Ciledug to increase their English language proficiency. The method of the program is offline by giving workshop and giving feedback to the students. Pre-test is conducted before the program by giving the students some questions related to Present forms. Also, the post-test is conducted to know their ability to measure and understand the Present forms concept after having this program.